2014
DOI: 10.7860/jcdr/2014/7578.4480
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Diagnosis of Helicobacter pylori: Evaluation of Two Enzyme Immunoassays, Testing Serum IgG and IgA Response in the Anand District of Central Gujarat, India

Abstract: Context: Validation of an accurate and less cumbersome noninvasive method to detect current Helicobacter pylori infection is a requisite for any laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…Compared to the stool Ag test, a sensitivity, specificity and agreement of 98.18, 97.78 and 98%, respectively were recorded for serum IgG Ab test (Table 2) These results were in accordance with the findings of Pandya et al, (Pandya et al, 2014), who reported that the IgG Ab test evaluated in their study, had a sensitivity of 100%, which permits the safe use of this test in screening surveys. Unlikely, Shah et al, (Shah et al, 2014), reported that serum IgG sensitivity ranged from 90 to 97%, but the specificity ranged from 50 to 96%.…”
Section: Resultssupporting
confidence: 89%
“…Compared to the stool Ag test, a sensitivity, specificity and agreement of 98.18, 97.78 and 98%, respectively were recorded for serum IgG Ab test (Table 2) These results were in accordance with the findings of Pandya et al, (Pandya et al, 2014), who reported that the IgG Ab test evaluated in their study, had a sensitivity of 100%, which permits the safe use of this test in screening surveys. Unlikely, Shah et al, (Shah et al, 2014), reported that serum IgG sensitivity ranged from 90 to 97%, but the specificity ranged from 50 to 96%.…”
Section: Resultssupporting
confidence: 89%
“…It was found that serum IgG Ab was positive in 19 of the 21 enrolled mothers (90%) with sensitivity, specificity and agreement of 94, 50 and 90%, respectively) ( Table 6). These results were in concordance with the findings of Pandya et al (2014) who reported that the IgG Abs evaluated in their study, had a sensitivity of 100% in adults, which permits the safe use of the test in epidemiologic surveys. Also, they recorded a very low specificity, indicating that the ELISA test must be validated for different populations (Pandya et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…These results were in concordance with the findings of Pandya et al (2014) who reported that the IgG Abs evaluated in their study, had a sensitivity of 100% in adults, which permits the safe use of the test in epidemiologic surveys. Also, they recorded a very low specificity, indicating that the ELISA test must be validated for different populations (Pandya et al, 2014). In addition, Shah et al (2014) reported that serum IgG sensitivity ranged between 90 and 97%, but the specificity ranged between 50 and 96%.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, (88.8%) have H. pylori -specific IgG antibodies (˃ 30-EIU) which reflect the high level of immune response to H. pylori as the mean of H. pylori -specific IgG antibodies (107.61 ± 52) EIU, which come in agreement with [ 20 ] and higher than [ 21 ] [ 22 ], reporting H. pylori seropositivity of 56.3%; 57% of Indian and Saudi Arabia patients respectively. The negative H. pylori -specific IgG (˂ 30-EIU) was detected in (11.3%) but, histologically the infection proved through detection of Cag A gene expression in gastric tissue.…”
Section: Discussionsupporting
confidence: 83%
“…H. pylori infection provokes both local and systemic antibody responses. The systemic response typically comprises a transient rise in IgM, followed by a rise in specific IgA and IgG maintained throughout infection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%